Extent of surgery for phaeochromocytomas in the genomic era. Issue 2 (17th January 2018) - Rossitti, H. M.; Söderkvist, P.; Gimm, O.
Abstract : Background: Germline mutations are present in 20–30 per cent of patients with phaeochromocytoma. For patients who develop bilateral disease, complete removal of both adrenal glands (total adrenalectomy) will result in lifelong adrenal insufficiency with an increased risk of death from adrenal crisis. Unilateral/bilateral adrenal‐sparing surgery (subtotal adrenalectomy) offers preservation of cortical function and independence from steroids, but leaves the adrenal medulla in situ and thus at risk of developing new and possibly malignant disease. Here, present knowledge about how tumour genotype relates to clinical behaviour is reviewed, and application of this knowledge when choosing the extent of adrenalectomy is discussed. Methods: A literature review was undertaken of the penetrance of the different genotypes in phaeochromocytomas, the frequency of bilateral disease and malignancy, and the underlying pathophysiological mechanisms, with emphasis on explaining the clinical phenotypes of phaeochromocytomas and their associated syndromes. Results: Patients with bilateral phaeochromocytomas most often have multiple endocrine neoplasia type 2 (MEN2) or von Hippel–Lindau disease (VHL) with high‐penetrance mutations for benign disease, whereas patients with mutations in the genes encoding SDHB (succinate dehydrogenase subunit B) or MAX (myelocytomatosis viral proto‐oncogene homologue‐associated factor X) are at increased risk of malignancy. Conclusion: Adrenal‐sparing surgery should be the standard approach for patients who have already been diagnosed with MEN2 or VHL when operating on the first side, whereas complete removal of the affected adrenal gland(s) is generally recommended for patients with SDHB or MAX germline mutations. Routine assessment of a patient's genotype, even after the first operation, can be crucial for adopting an appropriate strategy for follow‐up and future surgery. Abstract : Genotype dictates type of surgery